Peran Fungsi Manajemen dalam Pendidikan Islam: Sebuah Tinjauan Pustaka yang Sistematis - Hafiidh, Muhammad; Fauji, Imam (STAI Ihyaul Ulum Gresik, 2024)
This study aims to understand and analyze the application of management functions in Islamic education, especially in the POAC aspect (Planning, Organizing, Implementing, and Controlling). This study applies the Systematic Literature Review (SLR) method by following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines in the process of selecting and analyzing literature related to management functions published from 2019 to 2024. A total of 10 articles were downloaded from the Lens.org database as a source of information. The results of the study indicated that in Islamic education, the planning role focuses on developing a curriculum that is in line with Islamic values and strengthening students' morals. The organizing function focuses on a flexible and cooperative institutional structure, while the actuating function is carried out through Islamic leadership that provides motivation and inspiration. The controlling function is carried out through evaluation based on spiritual accountability and ethical responsibility. This study states that the application of management functions in Islamic education aims not only to achieve operational efficiency, but also to internalize deep spiritual values. This finding offers a new view for Islamic education managers in maximizing the role of management based on Islamic principles.